Mathematical model for the mass transport in multiple porous scales. (September 2018) - Alean, Jader; Maya, Juan C.; Chejne, Farid
Abstract: The transport of species in a vegetable matrix was modelled and studied based on a phenomenological model, in which a solid composed by the cells, pores and tissues was considered. The model is able to predict the multi-scale mass transport by defining only one effective diffusion coefficient, which made by proposing an inter-scale resistance constant. This parameter is a measure of the difficulty to the mass transport between two scales. The model was successfully validated with experimental data on the mass transport in both an organic and an inorganic matrix, which demonstrate the versatility of the model herein proposed. Highlights: A mathematical model for the mass transport in multi-scale porous systems is developed. An only one effective diffusivity for the whole multi-scale porous system is deduced. The model is successfully validated with experimental data on the cacao drying and the CO2 chemisorption on CaO. An inter-scale resistance constant for connecting multiple scales is proposed.